2020
DOI: 10.1038/s41467-020-14768-1
|View full text |Cite|
|
Sign up to set email alerts
|

Entanglement of propagating optical modes via a mechanical interface

Abstract: Many applications of quantum information processing (QIP) require distribution of quantum states in networks, both within and between distant nodes [1]. Optical quantum states are uniquely suited for this purpose, as they propagate with ultralow attenuation and are resilient to ubiquitous thermal noise. Mechanical systems are then envisioned as versatile interfaces between photons and a variety of solid-state QIP platforms [2, 3]. Here, we demonstrate a key step towards this vision, and generate entanglement b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 39 publications
(40 reference statements)
2
45
0
Order By: Relevance
“…Moreover, this entanglement persists at room temperature with realistic losses, stable optical spring detunings, and accessible circulating powers. With experimentally stable parameters, we predict a maximum logarithmic negativity versus temperature of E N = 0.2 in this parameter space; considering parameters close to reported optomechanical entanglement experiments yields an average logarithmic negativity of E N = 0.3 (with about 1% measurement certainty) which agrees with the results reported there [23]. Furthermore, we found that entanglement is highly temperature dependent, yet lowering losses is more effective.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, this entanglement persists at room temperature with realistic losses, stable optical spring detunings, and accessible circulating powers. With experimentally stable parameters, we predict a maximum logarithmic negativity versus temperature of E N = 0.2 in this parameter space; considering parameters close to reported optomechanical entanglement experiments yields an average logarithmic negativity of E N = 0.3 (with about 1% measurement certainty) which agrees with the results reported there [23]. Furthermore, we found that entanglement is highly temperature dependent, yet lowering losses is more effective.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, for input involving two light sources, an optomechanical cavity can output entangled light [18][19][20][21][22]. This form of bipartite optical entanglement generation has been demonstrated experimentally using a vibrating silicon oxide membrane [23]. This work considers a cantilever micromirror in place of the silicon oxide membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, let us briefly discuss how to detect the L-M entanglement. As discussed above, the entanglement is calculated from the covariance matrix V, so we can obtain the wanted results by measuring the corresponding V. [41,[50][51][52] The state of magnon in YIG sphere can be acquired by adding an external microwave probe field through the YIG sphere and homodyning its output, while the microwave and optical field quadratures can be directly measured by homodyning their output fields too.…”
Section: Resultsmentioning
confidence: 99%
“…There entanglement is distributed via a mediator, without the mediator ever becoming entangled (see end of Appendix A for details). Since in real experiments the light might contain some degree of classical correlations, demonstrating entanglement between certain modes of light that were mediated by a mechanical oscillator [6,7] does not allow us to make unambiguous statements regarding genuine optomechanical entanglement.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Experiments in optomechanics now operate routinely in a regime in which effects predicted by quantum theory can be observed. This includes mechanical oscillators cooled to their ground state of center-of-mass motion [1,2], ponderomotive squeezing [3][4][5], entanglement between different light tones [6,7], entanglement between different mechanical oscillators [8,9], measurement back-action [10], back-action evasion [11][12][13], and optomechanical entanglement, that is, entanglement between the mechanical oscillator and light, in a pulsed regime [14,15].…”
Section: Introductionmentioning
confidence: 99%